A Matter of Trust: The Role of Communities in Energy Decision-Making, Gas-Fired Power Facilities, Case Study: Oakville and King Township, Ontario - Bird, Stephen (Université d'Ottawa | University of Ottawa, 2016)
This case study is actually two comparative case studies, both focused on the siting of gas electricity generation plants in the outskirts of the Greater Toronto Area. The communities are the Town of Oakville (west of Toronto) and King Township (north of Toronto). The proposed gas plants were part of a province-wide initiative to upgrade and increase generation capacity in the wake of decisions to close or upgrade coal and nuclear generation plants. Through 2006-07, the Ontario Power Authority (OPA) engaged in an integrated power system planning process to determine the need for new facilities, including the facilities in Oakville and King. Hearings on the power system plan were held in 2008. No issues were raised but the hearings only identified general regional needs, not specific sites. The hearings and Independent Electricity System Operator (IESO) process ultimately resulted in the successful siting of more than 30 electricity generation and transmission projects from 2006 until 2014. A competitive procurement process was used, in which developers would put together differing solutions (sites, facility design, locations) in response to a RFP (request for proposals). The province would assess the proposals through a point system. Many (but not all) of the issues discussed in these case studies were addressed by a set of recommendations for planning and siting by the OPA and the IESO in 2013, and by the merger of both entities in 2015. This case study includes a discussion of these recommendations in the discussion section.
Keywords: Energy Policy; Energy Regulation; Community engagement; Social licence to operate; Social Acceptance; Energy projects; Consultation; Public participation